Position of the Prosecutor before the ICC – Challenges and De Lege Ferenda Postulates - Janusz-Pohl, Barbara (The ICC at 25: Lessons Learnt, 2025)
This study analyses the position of the International Criminal Court (ICC) prosecutor, using two theses as the prism of the study. According to the first thesis, the position of this figure is closely linked to the structural “fluctuability” of proceedings based on the Rome Statute. The second thesis argues that the ICC prosecutor has a dualistic role, being both an officer of justice and a party to the jurisdictional proceedings. Within this role, the principle of opportunism plays a pivotal role. Simultaneously, that the gradual opportunism formula has been adopted is recognised. Thus, the examination of the advisability of prosecution becomes less critical as the proceedings progress. In this context, the prosecutor’s position is outlined against the background of the effectiveness of procedural functions. This paper consists of five parts: introduction, description of the model and the main research theses, compact overview of the essential formulas of the prosecutor’s activities, critical examination of selected prosecutorial actions, and final remarks. Among other things, the last propositions include a recommendation to reconsider modifying the accusatory principle by increasing prosecutorial discretion. This overview ignores the interaction between ICC bodies and the UN Security Council, as the mechanisms provided for in the Rome Statute to block prosecution by the Security Council’s decision is considered to have political rather than legal connotations.Keywords: ICC prosecutor, opportunism, directionality of prosecutor, accusatorial principle, statute, prosecutorial activities, structural fluctuability